Numerical simulation of the Heston Model under stochastic correlation - Long Teng; Matthias Ehrhardt; Michael Günther (International Journal of Financial Studies, 2018)
Stochastic correlation models have become increasingly important in financial markets. In order to be able to price vanilla options in stochastic volatility and correlation models, in this work, we study the extension of the Heston model by imposing stochastic correlations driven by a stochastic differential equation. We discuss the efficient algorithms for the extended Heston model by incorporating stochastic correlations. Our numerical experiments show that the proposed algorithms can efficiently provide highly accurate results for the extended Heston by including stochastic correlations. By investigating the effect of stochastic correlations on the implied volatility, we find that the performance of the Heston model can be proved by including stochastic correlations.
Keywords: 330; Heston model; stochastic correlation process; Ornstein-Uhlenbeck process; quadraticexponential scheme